How important are abstainers in presidential elections? A comparative analysis between Africa and Latin America - Christian H. C. A. Henning; Daniel Diaz; Andrea Lendewig; Svetlana Petri (Kiel University, Department of Agricultural Economics, Chair of Agricultural Policy, 2020)
Even in countries with well functioning democracies, not all people with the right to vote in a presidential election decide to cast a vote. In order to study the importance of abstention in presidential elections in Africa and Latin America, data from Senegal and Honduras was analyzed. These countries have experienced a decline in the voter turnout over the past elections, which means that the party systems are somehow failing to engage voters in recent years. The purpose of this paper is to understand how people choose a certain party or candidate, as well as, how they decide to either vote or abstain. Moreover, we are looking to determine whether non-voters could motivate the governments to design and implement efficient policies. To achieve this, we estimated nested multinomial logit models including the alternative Abstention. Then, to evaluate government performance, we derived indicators for accountability and capture. Also, to determine the optimal policy positions for the governmental parties, First Order Condition (FOC) and Second Order Condition (SOC) were estimated for different issues.
Keywords: Q18; C31; C35; C38; 330; probabilistic voter model; capture; accountability; agricultural policy; Africa; Latin America